Rayleigh-Taylor instability of an ultrathin foil accelerated by the radiation pressure of an intense laser. - Palmer,CAJ; Schreiber,J; Nagel,SR; Dover,NP; Bellei,C; Beg,FN; Bott,S; Clarke,RJ; Dangor,AE; Hassan,SM; Hilz,P; Jung,D; et al. (Phys Rev Lett, 2012)
We report experimental evidence for a Rayleigh-Taylor-like instability driven by radiation pressure of an ultraintense (10(21) W/cm(2)) laser pulse. The instability is witnessed by the highly modulated profile of the accelerated proton beam produced when the laser irradiates a 5 nm diamondlike carbon (90% C, 10% H) target. Clear anticorrelation between bubblelike modulations of the proton beam and transmitted laser profile further demonstrate the role of the radiation pressure in modulating the foil. Measurements of the modulation wavelength, and of the acceleration from Doppler-broadening of back-reflected light, agree quantitatively with particle-in-cell simulations performed for our experimental parameters and which confirm the existence of this instability.